Aβ42 pentamers/hexamers are the smallest detectable oligomers in solution - Martin Wolff (Nature Portfolio, 2017)
Abstract Amyloid β (Aβ) oligomers may play a decisive role in Alzheimer’s disease related neurodegeneration, but their structural properties are poorly understood. In this report, sedimentation velocity centrifugation, small angle neutron scattering (SANS) and molecular modelling were used to identify the small oligomeric species formed by the 42 amino acid residue long isoform of Aβ (Aβ42) in solution, characterized by a sedimentation coefficient of 2.56 S, and a radius of gyration between 2 and 4 nm. The measured sedimentation coefficient is in close agreement with the sedimentation coefficient calculated for Aβ42 hexamers using MD simulations at µM concentration. To the best of our knowledge this is the first report detailing the Aβ42 oligomeric species by SANS measurements. Our results demonstrate that the smallest detectable species in solution are penta- to hexamers. No evidences for the presence of dimers, trimers or tetramers were found, although the existence of those Aβ42 oligomers at measurable quantities had been reported frequently.